2011
DOI: 10.3109/14992027.2011.588965
|View full text |Cite
|
Sign up to set email alerts
|

A multicenter study on the audiometric findings of styrene-exposed workers

Abstract: Occupational exposure to styrene is a risk factor for hearing loss, and styrene-exposed workers should be included in hearing loss prevention programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 36 publications
2
25
1
2
Order By: Relevance
“…The worst PTA responses for a wide range of frequencies (0.25 -8 kHz) were found among individuals of the group exposed to the solvent [22][23][24] .…”
Section: Styrenementioning
confidence: 93%
See 1 more Smart Citation
“…The worst PTA responses for a wide range of frequencies (0.25 -8 kHz) were found among individuals of the group exposed to the solvent [22][23][24] .…”
Section: Styrenementioning
confidence: 93%
“…Focused on the plastic and fiberglass industries, six studies found a positive association between exposure to styrene and Hearing Loss (HL) 11,[20][21][22][23][24] , four of which featured styrene exposure levels below recommended limits [20][21][22][23] . The worst PTA responses for a wide range of frequencies (0.25 -8 kHz) were found among individuals of the group exposed to the solvent [22][23][24] .…”
Section: Styrenementioning
confidence: 99%
“…A recent multicentre, cross-sectional study (Morata et al 2011) of workers from Sweden, Finland, and Poland found an association between styrene exposure and poorer hearing thresholds than predicted by individuals' age (when compared with ANSI S3.44 annexes A and B). The effect of noise exposure, with a mean which varied across centres between 80 and 84 dBA, did not have a significant effect on hearing, except when in combination with styrene.…”
Section: Evidence Of the Adverse Effects Of Solvents On Pure-tone Thrmentioning
confidence: 98%
“…In literature, evidences that exposure to organic solvents (e.g., styrene) either alone or in combination with noise has ototoxic effects, have been largely described [7,[17][18][19]. In these last studies, the effect of styrene exposure was investigated with a complete set of auditory tests, including pure tone audiometry [17,19], speech recognition tests [18], and OAE-based tests [7], to estimate the damage at the level of the cochlear outer hair cells (OHCs).…”
Section: Introductionmentioning
confidence: 99%
“…In these last studies, the effect of styrene exposure was investigated with a complete set of auditory tests, including pure tone audiometry [17,19], speech recognition tests [18], and OAE-based tests [7], to estimate the damage at the level of the cochlear outer hair cells (OHCs).…”
Section: Introductionmentioning
confidence: 99%